Tellurium-containing polymers and compounds
By reacting cyclic (sulfur) ether-based compounds with tetrahalide to form a polymer containing Te ether-containing or sulfhydryl ether bonds, the problems of improving the selection and performance of existing materials are solved, and high refractive index and high sensitivity are achieved. Resist and optical materials.
Patent Information
- Application Number
- CN202380037402.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-02
- Filing Date
- 2023-05-02
- Publication Date
- 2024-12-13
AI Technical Summary
Although existing Te-containing compounds and resins are useful as resist materials or optical materials, their selection is limited, especially in improving the refractive index and sensitivity of resist materials.
By reacting a compound having a cyclic (sulfur) ether group with tellurium tetrahalide, polymers and compounds having ether bonds or sulfhydryl bonds of Te are formed, for the production of resist films and optical components.
It provides resist materials with high refractive index and high sensitivity, suitable for lithography and optical applications, improving the selectivity and performance of materials.
Smart Images

Figure BDA0005109266900000041 
Figure BDA0005109266900000051 
Figure BDA0005109266900000052
Abstract
Description
Technical Field
[0001] The present invention relates to tellurium-containing polymers and compounds. Background Art
[0002] Tellurium (Te) has properties such as electronegativity, ionization energy, and electron affinity comparable to those of oxygen, sulfur, and selenium. Patent Document 1 discloses that a compound and a resin containing Te are useful as a resist material or an optical article.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2020 / 226150 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] Although the compounds described in Patent Document 1 are useful in industry, the inventors have thought that if other types of Te-containing polymers can be provided, the selectivity of industrially useful materials can be further expanded. In particular, compounds containing Te and oxygen atoms or sulfur atoms have the possibility of increasing the refractive index or further increasing the sensitivity when used as resist materials. In view of this situation, the subject of the present invention is to provide a compound having an ether bond or a thioether bond with Te.
[0008] Solutions for solving problems
[0009] The inventors have solved the above-mentioned problems by reacting a compound having a cyclic (thio)ether group with tellurium tetrahalide. That is, the above-mentioned problems are solved by the following present invention.
[0010] Method 1
[0011] A polymer having tellurium in its main chain, which is obtained by reacting (A) a compound having a plurality of cyclic (thio)ether groups with (B) TeX4 (wherein X is a halogen atom).
[0012] Method 2
[0013] The polymer according to embodiment 1, wherein the above-mentioned (A) is a compound represented by formula (A1) described below.
[0014] Method 3
[0015] The polymer according to embodiment 2, wherein W in the above formula is a group represented by -Z-Ar-Z-, and Ar is an organic group having an aromatic ring or a heterocyclic ring.
[0016] Method 4
[0017] The polymer according to Embodiment 3, wherein the aforementioned Ar is a group represented by -Ar'-U-Ar'-,
[0018] Ar' is an aromatic group or a heterocyclic aromatic group,
[0019] U is a divalent organic group or a single bond.
[0020] Method 5
[0021] The polymer according to embodiment 1 or 2, wherein the cyclic (thio)ether group of (A) has a 3- to 5-membered ring structure.
[0022] Method 6
[0023] A method for producing a polymer according to any one of Embodiments 1 to 4, comprising the step of subjecting the (A) and the (B) to an addition reaction.
[0024] Method 7
[0025] The production method according to Embodiment 6, wherein the reaction is carried out in the presence of a Lewis acid.
[0026] Method 8
[0027] A composition comprising the polymer according to any one of aspects 1 to 4.
[0028] Method 9
[0029] The composition according to Embodiment 8, comprising a component selected from the group consisting of a solvent, an acid generator, an acid crosslinking agent, and a combination thereof.
[0030] Method 10
[0031] A resist film formed from the composition according to Embodiment 8.
[0032] Method 11
[0033] A pattern forming method, comprising:
[0034] A film forming step of forming a film on a substrate using the composition described in Embodiment 8;
[0035] an exposure step of exposing the film to light; and
[0036] A developing step is a step of developing the film exposed in the above-mentioned exposure step to form a pattern.
[0037] Method 12
[0038] A photolithography underlayer film formed using the composition described in Embodiment 8.
[0039] Method 13
[0040] An optical component formed using the composition described in Embodiment 8.
[0041] Method 14
[0042] A tellurium-containing compound obtained by reacting (a) a compound having one cyclic (thio)ether group with (B) (B) TeX4 (wherein X is a halogen atom).
[0043] Method 15
[0044] A composition comprising the tellurium-containing compound according to embodiment 14.
[0045] Method 16
[0046] A purification method comprising:
[0047] a step of dissolving the tellurium-containing polymer according to any one of Embodiments 1 to 4 or the tellurium-containing compound according to Embodiment 14 in a solvent to obtain a solution, wherein the solvent comprises an organic solvent that is immiscible with water; and
[0048] The first extraction step is to bring the obtained solution into contact with an acidic aqueous solution to extract impurities in the polymer or compound.
[0049] Effects of the Invention
[0050] According to the present invention, a polymer and a compound having an ether bond or a thioether bond with Te can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 is the BPAO obtained in Example 1 1 H-NMR and 13 C-NMR spectrum.
[0052] Figure 2 is the reaction solution obtained in run 1 to run 5 in Table 1 1 H-NMR spectrum.
[0053] Figure 3 is the purified polymer obtained in Example 1 1 H-NMR spectrum.
[0054] Figure 4 This is a photograph of the film obtained in Example 2.
[0055] Figure 5 is the compound obtained in Example 3 1 H-NMR spectrum.
[0056] Figure 6 is the tBPO obtained in Example 4 1H-NMR spectrum.
[0057] Figure 7 is the polymer obtained in Example 7 1 H-NMR spectrum. DETAILED DESCRIPTION
[0058] The present invention is described in detail below. In the present invention, "X to Y" include both extreme values.
[0059] 1. Polymer
[0060] The polymer of the present embodiment is obtained by reacting (A) a compound having a plurality of cyclic (thio)ether groups with (B) TeX4 (wherein X is a halogen atom).
[0061] (1) (A) Compounds having multiple cyclic (thio)ether groups
[0062] The compound having multiple cyclic (thio)ether groups (hereinafter also referred to as "compound A") has multiple cyclic ether or cyclic thioether groups. The structure of the cyclic ether or cyclic thioether group is not limited, but is preferably a 3- to 5-membered ring structure, more preferably a 3- or 4-membered ring structure.
[0063] The compound A is preferably represented by the following formula.
[0064]
[0065] In the formula, Z is O or S, and the cyclic structure including Z represents a group having a cyclic ether or cyclic thioether group. n represents the number of the group and is 2 to 4, and varies depending on the valence of W. From the viewpoint of easy availability, n is preferably 2 or 3, preferably 2. The group having a cyclic ether or cyclic (thio)ether group is preferably represented by the following formula (C1) or (C2). In the formula, R 1 is an alkylene group having 1 to 3 carbon atoms, R 2 is an alkyl group with 1 to 3 carbon atoms, R 4 R is independently a hydrogen atom or an alkyl group having 1 or 2 carbon atoms. 4 Preferred is a hydrogen atom.
[0066]
[0067] Formula (C1) or (C2) is more preferably represented by the following formula (C1-1) or (C2-1). 2 Preferred is a methyl group or an ethyl group, and more preferred is a methyl group.
[0068]
[0069] W is an organic group having 10 to 30 carbon atoms. The organic group is not limited, but is preferably a group having an aromatic group or a heterocyclic aromatic group. In one embodiment, W is a group represented by -Z-Ar-Z-. That is, in this embodiment, n is 2 in formula (A1). Ar is an organic group having an aromatic ring, and Z is O or S as described above. Ar may have a monocyclic structure or a polycyclic structure.
[0070] In a preferred embodiment, Ar is represented by -Ar'-U-Ar'-. Ar' is an aromatic group or a heterocyclic aromatic group. In this case, compound A is represented by the following formula.
[0071]
[0072] Ar' is not limited, and is preferably phenylene, naphthylene, anthracenediyl, phenanthrenediyl, pyrenediyl or fluorenediyl. These groups may also have substituents. "Substitution" means that one or more hydrogen atoms in a functional group are replaced by a substituent unless otherwise specified. The "substituent" is not particularly limited, and examples thereof include a halogen atom, a hydroxyl group, a cyano group, a nitro group, a mercapto group, a heterocyclic group, a straight-chain aliphatic hydrocarbon group having 1 to 20 carbon atoms, a branched aliphatic hydrocarbon group having 3 to 20 carbon atoms, a cyclic aliphatic hydrocarbon group having 3 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an amino group having 0 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an acyl group having 1 to 20 carbon atoms, an alkoxycarbonyl group having 2 to 20 carbon atoms, an alkanoyloxy group having 1 to 20 carbon atoms, an aryloyloxy group having 7 to 30 carbon atoms, or an alkylsilyl group having 1 to 20 carbon atoms.
[0073] U is a connecting group, specifically a divalent organic group or a single bond. The organic group here is not limited, and from the viewpoint of ease of acquisition, it is a heteroatom, or a divalent hydrocarbon group with 1 to 40 carbon atoms that optionally contains a heteroatom. The heteroatom refers to an atom other than a hydrogen atom and a carbon atom, and examples thereof include an oxygen atom, a nitrogen atom, a sulfur atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, and a silicon atom. From the viewpoint of ease of acquisition of raw materials, sulfur atom, oxygen atom, nitrogen atom, or silicon atom is preferred. As a divalent hydrocarbon group with 1 to 40 carbon atoms, linear, branched, or cyclic alkylene groups with 1 to 40 carbon atoms, aralkylene groups with 6 to 40 carbon atoms, and the like can be cited. From the viewpoint of ease of synthesis, U is preferably a single bond; a divalent heteroatom; a sulfone group; a linear, branched, or cyclic alkylene group with 1 to 40 carbon atoms; an aralkylene group with 6 to 40 carbon atoms, among which divalent alkylene groups with 1 to 5 carbon atoms are preferred, and methylene and isopropylidene are particularly preferred. In particular, the -Ar'-U-Ar'- group is preferably a group derived from bisphenol A, bisphenol F, or bisphenol S. As described later, compound A may be a compound (BPAO) synthesized from bisphenol A and 3-(chloromethyl)-3-methyloxetane. In this case, -Ar'-U-Ar'- is derived from bisphenol A, and U is an isopropylidene group, Ar' is a phenylene group, and Z is an oxygen atom. Furthermore, the cyclic structure containing Z is a group derived from 3-(chloromethyl)-3-methyloxetane.
[0074] In another embodiment, W is a group represented by Ar-(Z-)3. That is, in this embodiment, n in formula (A1) is 3. Ar is an organic group having an aromatic ring, and Z is O or S as described above, and is bonded to the aforementioned cyclic structure including Z. Ar may have a monocyclic structure or a polycyclic structure.
[0075] In a preferred embodiment, W is represented by U-(Ar'-Z-)3. U is a trivalent linking group, preferably a trivalent linking group having 1 to 3 carbon atoms. Ar' is an aromatic group or a heterocyclic aromatic group. In this case, compound A is represented by the following formula.
[0076]
[0077] A preferred embodiment of the linking group U in the formula (A3) is a CH group and is represented by the following formula (A4). Ar' and Z in the formula (A3) are defined as in the above-mentioned formula (A2).
[0078]
[0079] (2)(B)TeX4
[0080] TeX4 (hereinafter also referred to as "compound B") is tellurium tetrahalide. X is a halogen, preferably F, Cl, or Br, and more preferably Cl.
[0081] (3) Structure of polymer
[0082] The polymer of this embodiment is obtained by addition reaction of compound A and compound B. Through this reaction, Te is bonded to O or S derived from compound A to form a polymer. The estimated structure when compound A2 is used as compound A is shown below.
[0083]
[0084] In the formula, Y is an alkylene group derived from a group having a cyclic (thio) ether group. The reaction is an addition reaction, and the obtained polymer has a bond between Te and O or S in the main chain. When the amount of compound B is set to an excess amount, a prominent high molecular weight component is generated, so that the molecular weight distribution becomes multimodal. The reason is speculated to be: since compound B has Lewis acid properties, compound A will undergo ring-opening polymerization alone. However, when compound A and B are put in a molar ratio close to equimolar, ring-opening polymerization of compound A alone will not be caused. In summary, it is speculated that the aforementioned polymer is generated by the addition reaction of compound A and B, and is the above-mentioned structure.
[0085] For example, the estimated structure of a polymer synthesized using a compound having a bisphenol A skeleton and two oxetane rings (hereinafter also referred to as "BPAO") as compound A and TeCl4 as compound B is as follows.
[0086]
[0087] In addition, when compound A is a trifunctional compound as shown in formula (A3), the obtained polymer becomes a multi-branched polymer having a multi-branched structure. A multi-branched polymer refers to a polymer having a branch extending from a main chain, but the length of the branch is not enough to form a gel. For example, a multi-branched polymer has the following inferred structure.
[0088]
[0089] n is the number of repeating units of the main chain, r is the number of repeating units of the side chain, and n>r. If r is too large, gelation will occur, and if r is too small, the solubility in the solvent will decrease. In one embodiment, r can be about 10 to 60% of n.
[0090] The estimated structure of a multi-branched polymer obtained from MTPOX and TeCl4 is shown below as an example when compound A is a trifunctional compound represented by formula (A3).
[0091]
[0092] (4) Characteristics
[0093] The polymer contains Te. Te easily absorbs ultraviolet rays. Therefore, the polymer is useful as a resist material. In addition, the polymer is transparent and has a high refractive index due to the Te-O or Te-S bond. Therefore, the polymer is also useful as an optical component.
[0094] 2. Compounds
[0095] The compound of this embodiment is obtained by reacting (a) a compound having one cyclic (thio)ether group (hereinafter also referred to as "compound a") with compound B. Compound a is as described for compound A except that there is one cyclic (thio)ether group. For example, compound a is preferably represented by the following formula.
[0096]
[0097] In the formula, Z is O or S, and the definition of the cyclic structure including Z is the same as that in compound A.
[0098] W" is an organic group having 1 to 30 carbon atoms or a halogen atom. The organic group is not limited, but is preferably a group having an alkyl group, an aromatic group or a heterocyclic aromatic group. The alkyl group here is preferably a linear, branched or cyclic alkyl group having 1 to 30 carbon atoms. In one embodiment, W is a group having an aromatic group or a heterocyclic aromatic group, preferably a group represented by -Z-Ar". Ar" is an aromatic group or a heterocyclic aromatic group, and may have a monocyclic structure or a polycyclic structure. In a preferred embodiment, Ar" is phenyl, naphthyl, anthracenyl, phenanthrenyl, pyrene or fluorenyl. These groups may also have substituents. "Substitution" means that one or more hydrogen atoms in a functional group are replaced by a substituent unless otherwise specified. The "substituent" is not particularly limited, and preferably includes, for example, a halogen atom, a hydroxyl group, a cyano group, a nitro group, a mercapto group, a heterocyclic group, a linear alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, a cyclic alkyl group having 3 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an amino group having 0 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an acyl group having 1 to 20 carbon atoms, an alkoxycarbonyl group having 2 to 20 carbon atoms, an alkanoyloxy group having 1 to 20 carbon atoms, an aroyloxy group having 7 to 30 carbon atoms, or an alkylsilyl group having 1 to 20 carbon atoms. Among these, the substituent is preferably a linear or branched alkyl group having 1 to 6 carbon atoms.
[0099] For example, the scheme and estimated structure of the compound synthesized using 3-(chloromethyl)-3-methyloxetane as compound a and TeCl4 as compound B are shown below.
[0100]
[0101] The halogen (Cl in the exemplary compound) bonded to the alkyl group of the compound can be converted to other functional groups as shown in the following scheme. For example, the compound converted to a polymerizable functional group is useful as a polymer having Te. In the following scheme, R is an organic group.
[0102]
[0103] In addition, the scheme and estimated structure of the compound synthesized using 3-(p-tBu-phenoxy)-3-methyloxetane as compound a and TeCl4 as compound B are shown below.
[0104]
[0105] The halogen (Cl in the exemplary compound) bonded to the alkyl group of the compound can be converted into other functional groups as described above.
[0106] 3. Method for producing polymer
[0107] The polymer compound of the present embodiment can be manufactured by subjecting compound A to addition reaction with compound B. The reaction conditions are not limited. In one embodiment, the temperature is in the range of -70°C to 200°C, preferably 0°C to 80°C, more preferably 20 to 50°C, and further preferably room temperature (20°C). In addition, for the atmosphere, it is preferably implemented under normal pressure and nitrogen, and the reaction can also be carried out under vacuum. A solvent can be used in the reaction. The solvent is not limited. Halogenated hydrocarbons such as chloroform, dichloromethane, chlorobenzene, ether compounds such as tetrahydrofuran, dioxane, and aromatic compounds such as benzene, toluene and nitrobenzene can be used, and non-protonic and polar compounds such as dimethyl sulfoxide, 1-methyl 2-pyrrolidone, dimethylformamide, and dimethylacetamide can be used. Te of compound B reacts with two cyclic (sulfide) ether groups. Therefore, it is preferred to determine the molar number of the two in a manner such that the cyclic (sulfide) ether equivalent in compound A and the Te equivalent of compound B are near 1:1. The cyclic (thio) ether equivalent and Te equivalent can be set to about 1: (0.7 to 1.2). As a catalyst, Lewis acids such as aluminum chloride, tin chloride, and boron trichloride are preferably used. The amount is not limited, but is about 0.01 to 0.1 equivalent relative to compound A. However, since boron trifluoride diethyl ether may promote the self-polymerization of compound A, it is preferred to adjust its amount appropriately.
[0108] 4. Method for producing the compound
[0109] The polymer compound of the present embodiment can be produced by subjecting compound A or compound a to an addition reaction with compound B. The reaction conditions and the like are as described in the method for producing the polymer.
[0110] 5. Composition
[0111] [Composition]
[0112] A composition comprising a polymer synthesized from the aforementioned compound A and compound B, a compound synthesized from the aforementioned compound A or compound a and compound B, or a polymer derived from the compound is useful as a lithography material, a lithography material composition, a resist underlayer film forming composition, and an optical article forming composition.
[0113] [Materials for photolithography]
[0114] The photolithography material is a material that can be used in photolithography technology and can be used as a photolithography material composition, and can be further used for resist applications (i.e., resist compositions), intermediate layer formation applications (i.e., intermediate layer formation compositions), lower film formation applications (i.e., lower film formation compositions), etc.
[0115] Lithography materials can be used for resist compositions, etc., which can reduce film defects (film formation), have good storage stability, are highly sensitive, have high refractive index and transparency in a specific wavelength region, and can impart good resist pattern shapes. Lithography materials are owing to containing Te, and therefore can be expected to have a sensitizing effect, particularly in lithography utilizing EUV. Among all elements, the high sensitizing effect that Te has is second only to xenon. Lithography materials may not contain a solvent.
[0116] [Material composition for lithography]
[0117] The photolithography material composition comprises the photolithography material and solvent of the present embodiment. The photolithography material composition can reduce the defects of the film (film formation), give a good resist pattern shape, and form a film with high etching resistance. In addition, the photolithography material composition has good storage stability, and can form a resist pattern with high sensitivity and a high refractive index and transparency in a specific wavelength region.
[0118] (Physical properties of lithography material composition, etc.)
[0119] As described above, the photolithography material can be used for resist applications, and an amorphous film can be formed by a known method such as spin coating. In addition, depending on the type of developer used, any of a positive resist pattern and a negative resist pattern can be distinguished. Hereinafter, the case where a photolithography material composition containing the photolithography material of the present embodiment is used for resist applications (as a resist composition) is described.
[0120] When the photolithography material composition is a positive resist pattern, the dissolution rate of the amorphous film formed by spin coating the photolithography material composition in the developer at 23°C is preferably The following are more preferably More preferably If the dissolution rate is Below, it is possible to prepare a resist that is insoluble in a developer. If the dissolution rate is above 100%, the resolution may be improved. It is speculated that this is because the solubility of the polymer or compound before and after exposure changes, so that the contrast between the exposed part dissolved in the developer and the unexposed part not dissolved in the developer at the interface becomes larger. In addition, it has the effect of reducing line edge roughness and defects.
[0121] When the photolithography material composition is a negative resist pattern, the dissolution rate of the amorphous film formed by spin coating the photolithography material composition in the developer at 23° C. is preferably If the dissolution rate is If the above, it is easily soluble in the developer, and is more suitable as a resist. If the dissolution rate is higher than 10%, the resolution is sometimes improved. It is speculated that this is because the microscopic surface parts of the aforementioned polymer or compound are dissolved, reducing the line edge roughness. In addition, it has the effect of reducing defects. The aforementioned dissolution rate can be determined by immersing the amorphous film in a developer for a specified time at 23°C and measuring the film thickness before and after immersion by known methods such as visual inspection, ellipsometer or QCM method.
[0122] When the photolithography material composition is a positive resist pattern, the dissolution rate of the portion of the amorphous film formed by spin coating the photolithography material composition exposed to radiation such as KrF excimer laser, extreme ultraviolet rays, electron beams or X-rays in the developer at 23°C is preferably If the dissolution rate is If the above, it is easily soluble in the developer, and is more suitable as a resist. If the dissolution rate is higher than 10%, the resolution may be improved. This is probably because the microscopic surface of the polymer or compound is dissolved, reducing the roughness of the line edge. In addition, it has the effect of reducing defects.
[0123] When the photolithography material composition is a negative resist pattern, the dissolution rate of the portion of the amorphous film formed by spin coating the photolithography material composition exposed to radiation such as KrF excimer laser, extreme ultraviolet rays, electron beams or X-rays in the developer at 23°C is preferably The following are more preferably More preferably If the dissolution rate is Below, it is possible to prepare a resist that is insoluble in a developer. If the dissolution rate is above 100%, the resolution may also be improved. It is speculated that this is because the solubility of the polymer or compound before and after exposure changes, so that the contrast at the interface between the unexposed part dissolved in the developer and the exposed part not dissolved in the developer becomes larger. In addition, it has the effect of reducing line edge roughness and defects.
[0124] (Other components of the lithography material composition)
[0125] The photolithography material composition contains the aforementioned polymer or compound as a solid component, and further contains a solvent. The solvent used in the photolithography material composition is not particularly limited, and the solvent disclosed in Patent Document 1 can be used. The solvent is preferably a safe solvent, more preferably at least one selected from PGMEA, PGME, CHN, CPN, 2-heptanone, anisole, butyl acetate, ethyl propionate and ethyl lactate, and more preferably at least one selected from PGMEA, PGME and CHN.
[0126] In the lithography material composition, the relationship between the solid content and the solvent content is not particularly limited, and the following conditions may be satisfied when the total mass of the solid content and the solvent is 100 mass %.
[0127] Solid content 1-80% by mass: Solvent 20-99% by mass
[0128] Solid content 1-50% by mass: Solvent 50-99% by mass
[0129] Solid content 2-40% by mass: Solvent 60-98% by mass
[0130] Solid content 2-10% by mass: Solvent 90-98% by mass
[0131] The lithography material composition may contain at least one selected from the group consisting of an acid generator (C), an acid crosslinking agent (G), an acid diffusion controller (E), and other components (F) as other solid components.
[0132] In the photolithography material composition, the content of the above-mentioned polymer or compound (the total amount when used in combination) is not particularly limited, and is preferably 50 to 99.4% by mass of the total mass of the solid component (the sum of the solid components arbitrarily used such as the above-mentioned polymer, the above-mentioned compound, the acid generator (C), the acid crosslinking agent (G), the acid diffusion controller (E) and other components (F), the same below), more preferably 55 to 90% by mass, further preferably 60 to 80% by mass, and particularly preferably 60 to 70% by mass. In the case of the above-mentioned content, the resolution is further improved and the line edge roughness (LER) becomes smaller.
[0133] (Acid Generator (C))
[0134] The lithography material composition preferably contains one or more acid generators (C) that directly or indirectly generate an acid by irradiation with any radiation selected from visible light, ultraviolet light, excimer laser, electron beam, extreme ultraviolet light (EUV), X-ray and ion beam.
[0135] In this case, the content of the acid generator (C) in the photolithography material composition is preferably 0.001 to 49 mass %, more preferably 1 to 40 mass %, further preferably 3 to 30 mass %, and particularly preferably 10 to 25 mass % of the total mass of the solid component. By using the acid generator (C) within the above content range, a pattern profile with higher sensitivity and lower edge roughness can be obtained.
[0136] The method of generating the acid in the photolithography material composition is not limited as long as the acid is generated in the system. If an excimer laser is used instead of ultraviolet rays such as g-line and i-line, finer processing can be performed. In addition, if electron beams, extreme ultraviolet rays, X-rays, and ion beams are used as high-energy beams, further fine processing can be performed.
[0137] The acid generator (C) is not particularly limited, and for example, compounds disclosed in International Publication No. 2017 / 033943 can be cited. As the acid generator (C), an acid generator having an aromatic ring is preferred, and an acid generator having a sulfonate ion having an aromatic group is more preferred, and diphenyltrimethylphenylsulfonium p-toluenesulfonate, triphenylsulfonium p-toluenesulfonate, triphenylsulfonium trifluoromethanesulfonate, and triphenylsulfonium nonafluoromethanesulfonate are particularly preferred. By using the acid generator, the line edge roughness can be reduced.
[0138] The photolithography material composition preferably further contains a naphthoquinone diazo photoactive compound described in Patent Document 1 as an acid generator. From the viewpoint of low roughness and solubility, a non-polymer naphthoquinone diazo photoactive compound is preferred, and a low molecular weight compound with a molecular weight of 1500 or less is more preferred, a molecular weight of 1200 or less is further preferred, and a molecular weight of 1000 or less is particularly preferred. As a preferred specific example of such a non-polymer naphthoquinone diazo photoactive compound, a non-polymer naphthoquinone diazo photoactive compound disclosed in International Publication No. 2016 / 158881 can be cited. The aforementioned acid generator (C) can be used alone or in combination of two or more.
[0139] (Acid crosslinking agent (G))
[0140] When the photolithography material composition is used as a negative resist material or as an additive for increasing pattern strength in a positive resist material, it is preferred to contain one or more acid crosslinking agents (G). The acid crosslinking agent (G) refers to a compound that can crosslink the aforementioned polymer or compound within or between molecules in the presence of an acid generated by an acid generator (C). Such an acid crosslinking agent (G) is not particularly limited, and examples thereof include compounds having one or more groups (hereinafter referred to as "crosslinking groups") that can crosslink the aforementioned polymer or compound.
[0141] Specific examples of such a crosslinkable group are not particularly limited, and examples thereof include those described in Patent Document 1. As the crosslinkable group of the acid crosslinking agent (G), a hydroxyalkyl group, an alkoxyalkyl group, and the like are preferred, and an alkoxymethyl group is particularly preferred.
[0142] The acid crosslinking agent (G) having the crosslinkable group is not particularly limited, and those described in Patent Document 1 can be exemplified.
[0143] As the acid crosslinking agent (G), there can be used compounds having a phenolic hydroxyl group as described in Patent Document 1, and compounds and resins which introduce the above crosslinking groups into acidic functional groups in alkali-soluble resins to impart crosslinking properties.
[0144] In the lithography material composition, the acid crosslinking agent (G) is preferably an alkoxyalkylated urea compound or its resin, or an alkoxyalkylated glycoluril compound or its resin (acid crosslinking agent (G1)), a phenol derivative having 1 to 6 benzene rings in the molecule and having 2 or more hydroxyalkyl groups or alkoxyalkyl groups in the molecule as a whole, and the hydroxyalkyl group or alkoxyalkyl group is bonded to any of the aforementioned benzene rings (acid crosslinking agent (G2)), and a compound having at least one α-hydroxyisopropyl group (acid crosslinking agent (G3)). For example, the compounds disclosed in International Publication No. 2017 / 033943 can be cited.
[0145] In the photolithography material composition, the content of the acid crosslinking agent (G) is preferably 0.5 to 49% by mass of the total mass of the solid component, more preferably 0.5 to 40% by mass, further preferably 1 to 30% by mass, and particularly preferably 2 to 20% by mass. If the content ratio of the above-mentioned acid crosslinking agent (G) is set to 0.5% by mass or more, the effect of suppressing the solubility of the resist film in the alkaline developer can be improved, the residual film rate can be reduced, and the swelling or meandering of the pattern can be suppressed, so it is preferred. On the other hand, if it is set to 49% by mass or less, it is preferred to suppress the decrease in heat resistance as a resist.
[0146] The content of at least one compound selected from the acid crosslinking agent (G1), the acid crosslinking agent (G2), and the acid crosslinking agent (G3) in the acid crosslinking agent (G) is not particularly limited and can be set to various ranges depending on the type of substrate used when forming the resist pattern.
[0147] (Acid diffusion control agent (E))
[0148] The photolithography material composition may contain an acid diffusion controller (E), which has the function of controlling the diffusion of the acid generated by the acid generator in the resist film due to radiation exposure, preventing the effect of the unpreferable chemical reaction under the unexposed area, etc. By using such an acid diffusion controller (E), the storage stability of the photolithography material composition is improved. In addition, the resolution can be further improved, and the line width variation of the resist pattern caused by the change of the temporary placement time before the radiation exposure and the temporary placement time after the radiation exposure can be suppressed, thereby becoming a very excellent person in process stability.
[0149] Such an acid diffusion controller (E) is not particularly limited, and examples thereof include radiation-decomposable basic compounds such as nitrogen-containing basic compounds, basic sulfonium compounds, and basic iodonium compounds. Examples of the acid diffusion controller (E) include compounds disclosed in International Publication No. 2017 / 033943. The acid diffusion controller (E) may be used alone or in combination of two or more.
[0150] The content of the acid diffusion controller (E) is preferably 0.001 to 49% by mass of the total mass of the solid component, more preferably 0.01 to 10% by mass, further preferably 0.01 to 5% by mass, and particularly preferably 0.01 to 3% by mass. If the content of the acid diffusion controller (E) is within the above range, the degradation of the resolution, the pattern shape, the dimensional fidelity, etc. can be further suppressed. Moreover, even if the temporary placement time from electron beam irradiation to heating after radiation irradiation becomes longer, the shape of the upper layer of the pattern will not deteriorate. In addition, if the content of the acid diffusion controller (E) is less than 10% by mass, the sensitivity, the developability of the unexposed part, etc. can be prevented from being reduced. And by using this acid diffusion controller, the storage stability of the photolithography material composition is improved, and the resolution is improved, and the line width change of the resist pattern caused by the change of the temporary placement time before radiation irradiation and the temporary placement time after radiation irradiation can be suppressed, thereby becoming a person with excellent process stability.
[0151] (Other ingredients (F))
[0152] In the scope of not hindering the purpose of the present embodiment, one or more dissolution promoters, dissolution control agents, sensitizers, surfactants, and various additives such as organic carboxylic acids or phosphorus oxoacids or their derivatives may be added to the photolithography material composition as other components (F) as needed. As other components (F), for example, compounds disclosed in International Publication No. 2017 / 033943 can be cited.
[0153] The total content of other components (F) is preferably 0 to 49% by mass, more preferably 0 to 5% by mass, further preferably 0 to 1% by mass, particularly preferably 0% by mass, based on the total mass of the solid content.
[0154] In the lithography material composition, the contents of the aforementioned polymer or compound, the acid generator (C), the acid diffusion controller (E), and the other components (F) (the aforementioned polymer or compound (total when used in combination) / acid generator (C) / acid diffusion controller (E) / other components (F)) are as follows in terms of mass % based on solid matter.
[0155] Preferably, 50 to 99.4 / 0.001 to 49 / 0.001 to 49 / 0 to 49
[0156] More preferably, 55 to 90 / 1 to 40 / 0.01 to 10 / 0 to 5
[0157] More preferably, 60 to 80 / 3 to 30 / 0.01 to 5 / 0 to 1
[0158] Particularly preferably, it is 60 to 70 / 10 to 25 / 0.01 to 3 / 0.
[0159] The content ratio of each component is selected from various ranges so that the total amount thereof becomes 100 mass %. When the content ratio is set as the above, performances such as sensitivity, resolution, and developability are further excellent.
[0160] In one embodiment, the lithography material composition comprises the above-mentioned polymer or compound, an acid generator (C), and an acid crosslinking agent (G). In this case, the preferred amounts of the components are as follows in terms of mass % based on solids.
[0161] Preferably 30 to 99.4 / 0.001 to 49 / 0.001 to 49
[0162] More preferably, 35 to 90 / 1 to 40 / 1 to 40
[0163] More preferably, 40 to 80 / 1.5 to 30 / 2 to 30
[0164] Particularly preferably, 45 to 70 / 2 to 20 / 2 to 20
[0165] In this case, the lithography material composition may contain 0.001 to 2 mass % of the acid diffusion inhibitor (E) based on the solid content.
[0166] The method for preparing the lithography material composition is not particularly limited, and examples thereof include a method in which each component is dissolved in a solvent to form a uniform solution, and then filtered using a filter having a pore size of about 0.2 μm as required.
[0167] The photolithography material composition may include a resin within the scope of not hindering the purpose of the present invention. The resin is not particularly limited, and examples thereof include: novolac resin, polyvinylphenol, polyacrylic acid, polyvinyl alcohol, styrene-maleic anhydride resin, and polymers containing acrylic acid, vinyl alcohol or vinylphenol as monomer units or their derivatives. The content of the resin is not particularly limited, and is appropriately adjusted according to the type of the aforementioned polymer or compound, but is preferably 30 parts by mass or less relative to 100 parts by mass of the compound, more preferably 10 parts by mass or less, further preferably 5 parts by mass or less, and particularly preferably 0 parts by mass.
[0168] [Pattern Formation Method]
[0169] When a pattern is formed on a substrate using a photolithography material, for example, the following pattern forming method can be used, which includes: a film forming step of forming a film on a substrate using the photolithography material of the present embodiment or a composition containing the same (hereinafter, they are sometimes collectively referred to as "photolithography materials, etc."); an exposure step of exposing the aforementioned film; and a development step of developing the film exposed in the aforementioned exposure step to form a pattern.
[0170] For example, when a resist pattern is formed using a photolithography material, the method for forming the pattern (resist pattern) is not particularly limited, and as a suitable method, the following method can be cited, which includes: a film forming step of applying a resist composition including the above-mentioned photolithography material on a substrate to form a film (resist film); an exposure step of exposing the formed film (resist film); and a developing step of developing the film (resist film) exposed in the aforementioned exposure step to form a pattern (resist pattern). The resist pattern of this embodiment can also be formed as an upper resist in a multilayer process.
[0171] As a specific method for forming a resist pattern, it is not particularly limited, and for example, the following method can be cited. First, the aforementioned resist composition is applied on a substrate known in the past by a coating method such as spin coating, cast coating, and roll coating to form a resist film. The substrate known in the past is not particularly limited, and examples thereof include substrates for electronic components, those on which a specified wiring pattern has been formed, etc. More specifically, it is not particularly limited, but for example, metal substrates such as silicon wafers, copper, chromium, iron, and aluminum, glass substrates, etc. can be cited. As the material of the wiring pattern, it is not particularly limited, but for example, copper, aluminum, nickel, gold, etc. can be cited. In addition, an inorganic film or an organic film can be provided on the aforementioned substrate as needed. As an inorganic film, it is not particularly limited, and for example, an inorganic anti-reflection film (inorganic BARC) can be cited. As an organic film, it is not particularly limited, and for example, an organic anti-reflection film (organic BARC) can be cited. Surface treatment using hexamethyldisilazane, etc. can also be performed.
[0172] Next, the coated substrate is heated as needed. The heating conditions vary according to the composition contained in the resist composition, but are preferably 20 to 250°C, more preferably 20 to 150°C. By heating, the adhesion of the resist to the substrate is sometimes improved, so it is preferred. Next, the resist film is exposed to a desired pattern by any radiation selected from the group consisting of visible light, ultraviolet light, excimer laser, electron beam, extreme ultraviolet light (EUV), X-rays and ion beams. The exposure conditions are appropriately selected according to the compounding composition of the resist composition. In the method for forming a resist pattern, in order to stably form a high-precision fine pattern under exposure, it is preferably heated after the radiation irradiation. The heating conditions vary according to the compounding composition of the resist composition, but are preferably 20 to 250°C, more preferably 20 to 150°C.
[0173] Next, the exposed resist film is developed using a developer to form a predetermined resist pattern. As the developer, a solvent having a solubility parameter (SP value) close to that of the polymer or compound is preferably selected. Suitable solvents include those disclosed in Patent Document 1.
[0174] A surfactant may be added to the developer in an appropriate amount as required. The surfactant is not particularly limited, and for example, ionic or nonionic fluorine-based or silicon-based surfactants may be used. As these surfactants, those disclosed in Patent Document 1 may be cited. As the nonionic surfactant, a fluorine-based surfactant or a silicon-based surfactant is further preferably used.
[0175] The amount of the surfactant used is usually 0.001 to 5% by mass, preferably 0.005 to 2% by mass, and more preferably 0.01 to 0.5% by mass, based on the total amount of the developer.
[0176] As a developing method, for example, the following methods can be applied: a method of immersing a substrate in a tank filled with a developer for a certain period of time (immersion method); a method of allowing the developer to protrude on the surface of the substrate due to surface tension and remain stationary for a certain period of time to perform development (puddle method); a method of spraying the developer on the surface of the substrate (spray method); a method of scanning a developer discharge nozzle at a fixed speed on a substrate rotating at a fixed speed and discharging the developer at the same time (dynamic distribution method), etc. The time for pattern development is not particularly limited, and is preferably 10 seconds to 90 seconds. In addition, after the development process, the process of replacing with other solvents and stopping the development process can also be performed.
[0177] It is preferred that a step of washing with a washing liquid containing an organic solvent is included after development. As the washing liquid and the washing method used in the washing step after development, those disclosed in Patent Document 1 can be cited.
[0178] After forming the resist pattern, etching is performed to obtain a patterned wiring board. The etching method can be performed by a known method such as dry etching using plasma gas and wet etching using an alkaline solution, a cupric chloride solution, a ferric chloride solution, or the like.
[0179] After forming the resist pattern, plating may be performed. The plating method is not particularly limited, and examples thereof include copper plating, solder plating, nickel plating, and gold plating.
[0180] The remaining resist pattern after etching can be stripped by an organic solvent. As the organic solvent and the stripping method, those disclosed in Patent Document 1 can be cited.
[0181] The wiring substrate can also be formed by a lift-off method in which a metal is deposited in a vacuum after forming a resist pattern and then the resist pattern is dissolved with a solution.
[0182] [Resist underlayer film-forming composition, underlayer film for lithography, and pattern forming method]
[0183] (First Embodiment)
[0184] <Resist Underlayer Film-Forming Composition>
[0185] The resist lower film forming composition of the present embodiment is a resist lower film forming composition containing the aforementioned polymer or compound and a silicon-containing compound (e.g., a hydrolyzable organosilane, its hydrolyzate or its hydrolysis condensate). The carbon concentration of the resist lower film forming composition is relatively high, the oxygen concentration is relatively low, the heat resistance is high, and the solvent solubility is also high. Therefore, the rectangularity of the pattern is excellent. In addition, the defects of the film (film formation) can be reduced, the storage stability is good, it has high sensitivity and has a high refractive index and transparency in a specific wavelength region, and can give a good resist pattern shape.
[0186] The resist lower film forming composition can be suitably used, for example, in a multilayer resist method in which a resist lower film is also provided between an upper resist (photoresist, etc.) and a hard mask, an organic lower film, etc. In such a multilayer resist method, for example, a resist lower film is formed on its upper part by a coating method, etc., across an organic lower film or a hard mask on a substrate, and an upper resist (for example, a photoresist, an electron beam resist, an EUV resist) is formed on the resist lower film. Afterwards, a resist pattern is formed by exposure and development, and the resist pattern is used to dry-etch the resist lower film and perform pattern transfer, and the pattern is transferred by etching the organic lower film and the substrate is processed by the organic lower film.
[0187] That is, the resist lower film (photolithography lower film) formed using the resist lower film forming composition is not easy to cause intermixing with the upper resist and has heat resistance, for example, since the etching speed relative to the halogen (fluorine) etching gas is greater than the upper resist after patterning as a mask, a rectangular and good pattern can be obtained. Furthermore, the resist lower film formed using the resist lower film forming composition has high resistance to oxygen-based etching gas, so it can function as a good mask when the hard mask and other layers are patterned on the substrate. It should be noted that the resist lower film forming composition can also be used in the way that the resist lower film is multi-layered. In this case, the position (stacked on which layer) of the resist lower film formed using the resist lower film forming composition is not particularly limited, and can be directly below the upper resist, can be located at the layer closest to the substrate side, or can be a way clamped by the resist lower film.
[0188] In order to form a fine pattern and prevent the pattern from collapsing, there is a tendency to make the film thickness of the resist thinner. Due to the thin film of the resist, in the dry etching for transferring the pattern to the film present in the lower layer, if the etching speed is not higher than the film of the upper layer, the pattern transfer cannot be performed. In this embodiment, an organic lower film can be separated from the substrate, and the upper part thereof can be covered with the resist lower film (containing a silicon-based compound) of the present embodiment, and then the upper part thereof can be covered with a resist film (organic resist film). The film of the organic component and the film of the inorganic component will produce a large difference in the dry etching speed depending on the choice of the etching gas. The dry etching speed of the film of the organic component becomes higher under the oxygen-based gas, while the dry etching speed of the film of the inorganic component becomes higher under the halogen-containing gas.
[0189] For example, the resist underlayer film after pattern transfer can be used to dry-etch the organic underlayer film thereunder using an oxygen-based gas, and the pattern of the organic underlayer film can be transferred. The substrate can be processed using the organic underlayer film after pattern transfer using a halogen-containing gas.
[0190] In addition, the resist underlayer film formed by the resist underlayer film-forming composition includes the aforementioned polymer or compound containing Te having excellent absorption capacity for active light and includes a silicon-containing compound (e.g., a hydrolyzable organic silane, a hydrolyzate thereof, or a hydrolysis-condensate thereof), so that the sensitivity of the upper resist is improved, and intermixing with the upper resist is not caused, and the shape of the pattern of the resist underlayer film-forming film after exposure and development becomes a rectangular shape. This enables substrate processing with a fine pattern.
[0191] Furthermore, the resist underlayer film formed by the resist underlayer film forming composition of the present embodiment has high heat resistance and can be used even under high-temperature baking conditions. Furthermore, since the molecular weight is relatively low and the viscosity is low, even a substrate having steps (especially a fine pitch or hole pattern, etc.) can be easily filled into every corner, and as a result, there is a tendency that the planarization property or embedding property is relatively favorably improved.
[0192] The resist underlayer film forming composition may further include a solvent, an acid, an acid crosslinking agent, etc. in addition to the polymer or compound and the silicon-containing compound. Furthermore, an organic polymer compound, an acid generator and a surfactant, other water, an alcohol and a curing catalyst, etc. may be included as arbitrary components. From the viewpoint of coating properties and quality stability, the content of the compound and the resin of the present embodiment in the resist underlayer film forming composition is preferably 0.1 to 70% by mass, more preferably 0.5 to 50% by mass, and particularly preferably 3.0 to 40% by mass.
[0193] As the solvent, any known solvent can be appropriately used as long as it can dissolve at least the above-mentioned polymer or compound. The type and amount of the solvent can be set as disclosed in Patent Document 1.
[0194] The resist underlayer film-forming composition may contain an acid from the viewpoint of promoting curability. The type and amount of the acid may be set as disclosed in Patent Document 1.
[0195] The resist underlayer film-forming composition may contain one or more acid crosslinking agents when used as a negative resist material or as an additive for increasing pattern strength in a positive resist material. The acid crosslinking agent refers to a compound that can crosslink the polymer or compound intramolecularly or intermolecularly in the presence of the above-mentioned acid. The type and amount of the acid crosslinking agent can be set as disclosed in Patent Document 1.
[0196] The resist underlayer film-forming composition contains a silicon-containing compound. The silicon-containing compound may be an organic silicon-containing compound or an inorganic silicon-containing compound, and is preferably an organic silicon-containing compound. The type and amount of the silicon-containing compound may be set as disclosed in Patent Document 1.
[0197] The resist underlayer film-forming composition may contain, in addition to the above components, an organic polymer compound, a crosslinking agent, a photoacid generator, a surfactant, etc. as necessary. The types and amounts of these components can be set as disclosed in Patent Document 1.
[0198] <Underlayer film for lithography and pattern forming method>
[0199] The underlayer film for lithography of the present embodiment can be formed using the resist underlayer film-forming composition. The underlayer film for lithography of the present embodiment can be suitably used as an underlayer (resist underlayer film) of a photoresist (upper layer) used in a multilayer resist method.
[0200] In this embodiment, for example, a resist underlayer film is formed using a resist underlayer film-forming composition, at least one photoresist layer is formed on the resist underlayer film, and then a predetermined region of the photoresist layer is irradiated with radiation and developed to form a pattern.
[0201] In addition, as one mode of the pattern forming method of the first embodiment of the present invention using the anti-etching underlayer film forming composition of the first embodiment prepared by the above-mentioned operation, the following pattern forming method can be cited: an organic underlayer film is formed on a substrate using a coating-type organic underlayer film material, a resist underlayer film is formed on the aforementioned organic underlayer film using the anti-etching underlayer film forming composition of the first embodiment of the present invention, an upper resist film is formed on the aforementioned resist underlayer film using an upper resist film composition, an upper resist pattern is formed on the aforementioned upper resist film, the pattern is transferred to the aforementioned resist underlayer film by etching using the aforementioned upper resist pattern as a mask, the pattern is transferred to the aforementioned organic underlayer film by etching using the aforementioned resist underlayer film to which the pattern is transferred, and further the pattern is transferred to the aforementioned substrate (workpiece) by etching using the aforementioned organic underlayer film to which the pattern is transferred as a mask.
[0202] As another mode of the pattern forming method of the first embodiment, the following pattern forming method can be cited: an organic hard mask containing carbon as a main component is formed on a substrate by a CVD method, a resist underlayer film is formed on the aforementioned organic hard mask using the resist underlayer film forming composition of the first embodiment, an upper resist film is formed on the aforementioned resist underlayer film using an upper resist film composition, an upper resist pattern is formed on the aforementioned upper resist film, the upper resist pattern is used as a mask to transfer the pattern to the aforementioned resist underlayer film by etching, the aforementioned resist underlayer film to which the pattern is transferred is used as a mask to transfer the pattern to the aforementioned organic hard mask by etching, and further the aforementioned organic hard mask to which the pattern is transferred is used as a mask to transfer the pattern to the aforementioned substrate (workpiece) by etching.
[0203] As the aforementioned substrate, for example, a semiconductor substrate can be used. As the aforementioned semiconductor substrate, a silicon substrate can be generally used, but it is not particularly limited, and Si, amorphous silicon (α-Si), p-Si, SiO2, SiN, SiON, W, TiN, Al, etc., which are different from the processed layer, can be used. In addition, as the metal constituting the aforementioned substrate (processed object; including the aforementioned semiconductor substrate), those disclosed in Patent Document 1 can be used.
[0204] The pattern forming method of this embodiment can form an organic lower film or an organic hard mask on a substrate. Among them, the organic lower film can be formed by a coating type organic lower film material using a spin coating method, etc., and the organic hard mask can be formed by a material of an organic hard mask with carbon as the main component using a CVD method. Although the types of such organic lower film and organic hard mask are not particularly limited, when the upper resist film is patterned by exposure, it is preferred that the anti-reflective film function is fully exhibited. By forming such an organic lower film or organic hard mask, the pattern formed by the upper resist film can be transferred to the substrate (processed object) without generating a size conversion difference. It should be noted that a hard mask "with carbon as the main component" refers to a hard mask in which more than 50% by mass of the solid content is composed of a carbon-based material such as amorphous hydrogenated carbon represented by aC:H, which is called amorphous carbon. The aC:H film can be deposited by various techniques, and plasma chemical vapor deposition (PECVD) is widely used due to cost efficiency and the possibility of adjusting the film quality. As an example of the hard mask, for example, reference can be made to what is described in Japanese Unexamined Patent Application Publication No. 2013-526783.
[0205] For the resist lower film formed by using the resist lower film forming composition used in the pattern forming method of the present embodiment, it can be made by the resist lower film forming composition by spin coating on a workpiece provided with an organic lower film, etc. In the case of forming the resist lower film by spin coating, after spin coating, it is ideal to bake in order to evaporate the solvent and prevent intermixing with the upper resist film, and to promote the crosslinking reaction. The baking temperature is preferably in the range of 50 to 500°C. At this time, it varies depending on the structure of the manufactured device, but in order to reduce the thermal damage caused to the device, the baking temperature is particularly preferably below 400°C. The baking time is preferably adopted in the range of 10 seconds to 300 seconds.
[0206] In addition, in the pattern forming method of the present embodiment, as a method for forming a pattern on the upper resist film, any method among photolithography using light with a wavelength of less than 300nm or EUV light, electron beam direct drawing method, and directed self-assembly method can be appropriately used. By using such a method, a fine pattern can be formed on the resist upper film.
[0207] As the aforementioned upper resist film composition, it can be appropriately selected according to the above-mentioned method of forming a pattern in the upper resist film. For example, in the case of a photolithography method using light below 300nm or EUV light, as the upper resist film composition, a chemically amplified photoresist film material can be used. As such a photoresist film material, it can be exemplified: by forming a photoresist film and exposing it to the exposure portion using an alkali developer to dissolve and form a positive pattern, or by using a developer consisting of an organic solvent to dissolve the unexposed portion to form a negative pattern.
[0208] The resist underlayer film formed from the resist underlayer film-forming composition of the present embodiment may absorb light used in a photolithography process depending on the wavelength of the light, and in such a case, can function as an antireflection film having an effect of preventing light reflected from the substrate.
[0209] In addition, the lower film of the EUV resist can also be used for the following purposes in addition to the function as a hard mask. The aforementioned Te-containing resist lower film forming composition can be used as the lower anti-reflection film of the EUV resist, which can be non-intermixed with the EUV resist, and can prevent the unpreferable exposure light, such as the above-mentioned UV, DUV (ArF light, KrF light) from reflecting from the substrate or interface during EUV exposure (wavelength 13.5nm). Reflection can be effectively prevented in the lower layer of the EUV resist. In addition, the aforementioned lower film forming composition can show the sensitization of the upper resist composition due to the excellent absorption capacity of EUV, which helps to improve sensitivity. When used as the EUV resist lower film, the process can be carried out in the same way as the photoresist lower film.
[0210] (Second Embodiment)
[0211] <Resist Underlayer Film-Forming Composition>
[0212] The resist underlayer film-forming composition of the second embodiment can reduce film defects (thin film formation), has good storage stability, has high sensitivity, has a high refractive index and transparency in a specific wavelength region, and can impart a good resist pattern shape. The resist underlayer film-forming composition of this embodiment may not contain a silicon-containing compound.
[0213] The resist underlayer film forming composition of the present embodiment can be applied to wet process, can form a resist underlayer film with excellent resolution and sensitivity, and can achieve an excellent resist pattern after development. In addition, the resist underlayer film forming composition can be used to form a photoresist underlayer film with excellent heat resistance, step embedding characteristics and flatness and a useful resist underlayer film forming composition. In addition, the resist underlayer film forming composition is used to form a photoresist underlayer film with excellent heat resistance, step embedding characteristics and flatness. In addition, the resist underlayer film forming composition is used to form a compound with a specific structure with relatively high carbon concentration, relatively low oxygen concentration and high solvent solubility, so that the film degradation during baking can be suppressed and the etching resistance to fluorine gas system plasma etching, etc. is also excellent. And then, because the adhesion with the resist layer is also excellent, an excellent resist pattern can be formed. The resist underlayer film forming composition of the present embodiment is particularly excellent in heat resistance, step embedding characteristics and flatness, so it can be used as a composition for resist underlayer film formation, for example, arranged in the bottom layer in a multilayer resist layer. However, the resist underlayer film formed using the resist underlayer film-forming composition of the present embodiment may further include another resist underlayer between the resist underlayer film and the substrate.
[0214] The resist underlayer film forming composition of the present embodiment may further include a solvent, an acid generator, an acid crosslinking agent, etc. Furthermore, it may include a basic compound, other water, alcohol, and a curing catalyst as an arbitrary component. From the viewpoint of coatability and quality stability, the content of the aforementioned polymer or compound (in the case of combined use, the total) in the resist underlayer film forming composition is preferably 0.1 to 70% by mass, more preferably 0.5 to 50% by mass, and particularly preferably 3.0 to 40% by mass.
[0215] As the solvent used in the present embodiment, any known solvent can be used as appropriate as long as it dissolves at least the above-mentioned polymer or compound. The type and amount of the solvent can be set as disclosed in Patent Document 1.
[0216] The resist underlayer film-forming composition of the present embodiment may contain an acid crosslinking agent as necessary from the viewpoint of suppressing intermixing, etc. The type and amount of the acid crosslinking agent can be set as disclosed in Patent Document 1.
[0217] The resist underlayer film-forming composition of the present embodiment may contain an acid generator as necessary from the viewpoint of further promoting the crosslinking reaction by heat, etc. The type and amount of the acid generator can be set as disclosed in Patent Document 1.
[0218] Furthermore, the resist underlayer film forming composition of the present embodiment may contain a basic compound from the viewpoint of improving storage stability, etc. The type and amount of the basic compound can be set as disclosed in Patent Document 1.
[0219] The resist underlayer film-forming composition of the present embodiment may contain other resins or compounds for the purpose of imparting thermosetting properties or controlling absorbance. As such other resins or compounds, those disclosed in Patent Document 1 can be used.
[0220] <Resist underlayer film for lithography and pattern forming method>
[0221] The resist underlayer film for lithography according to the second embodiment is formed using the resist underlayer film forming composition according to the second embodiment. The pattern formed in this embodiment can be used as, for example, a resist pattern or a circuit pattern.
[0222] In addition, the pattern forming method of the second embodiment comprises: a step of forming a resist underlayer film on a substrate using the resist underlayer film forming composition of the second embodiment of the present invention (A-1 step); a step of forming at least one photoresist layer on the aforementioned resist underlayer film (A-2 step); and a step of irradiating radiation to a predetermined area of the aforementioned photoresist layer and developing it after forming at least one photoresist layer in the aforementioned A-2 step (A-3 step). It should be noted that the "photoresist layer" refers to the outermost layer of the resist layer, that is, the layer disposed on the outermost side (opposite to the substrate) of the resist layer.
[0223] Furthermore, another pattern forming method of the second embodiment of the present invention comprises: a step of forming a resist underlayer film on a substrate using the resist underlayer film forming composition of the second embodiment of the present invention (B-1 step); a step of forming a resist intermediate layer film on the aforementioned underlayer film using a resist intermediate layer film material (for example, a silicon-containing resist layer) (B-2 step); a step of forming at least one photoresist layer on the aforementioned resist intermediate layer film (B-3 step); after forming at least one photoresist layer in the aforementioned B-3 step, a step of irradiating a specified area of the aforementioned photoresist layer with radiation and developing it to form a resist pattern (B-4 step); and after forming the resist pattern in the aforementioned B-4 step, a step of etching the aforementioned resist intermediate layer film by using the aforementioned resist pattern as a mask, etching the aforementioned underlayer film using the obtained intermediate layer film pattern as an etching mask, and etching the substrate using the obtained underlayer film pattern as an etching mask, thereby forming a pattern on the substrate (B-5 step).
[0224] If the resist underlayer film for lithography of the present embodiment is formed by the resist underlayer film forming composition of the present embodiment, the formation method is not particularly limited, and a known method can be applied. For example, the resist underlayer film can be formed by applying the resist underlayer film forming composition of the present embodiment to a substrate using a known coating method or printing method such as spin coating or screen printing, and then removing the organic solvent by volatilization.
[0225] When forming the resist underlayer film, a baking treatment is preferably performed to suppress the intermixing phenomenon with the upper resist layer (eg, photoresist layer, resist intermediate layer film) and promote the crosslinking reaction.
[0226] After making the resist lower film on the substrate, a resist intermediate film can be set between the photoresist layer and the resist lower film. For example, in the case of a two-layer process, a silicon-containing resist layer or a common single-layer resist composed of hydrocarbons can be set on the resist lower film as the resist intermediate film. In addition, for example, in the case of a three-layer process, it is preferred to make a silicon-containing intermediate layer between the resist intermediate film and the photoresist layer, and then make a silicon-free single-layer resist layer thereon. As a photoresist material for forming these photoresists, resist intermediate films, and resist layers arranged between these layers, known ones can be used. As a silicon-containing resist material, those disclosed in patent document 1 can be used. In addition, a resist intermediate film formed by a chemical vapor deposition (CVD) method can also be used.
[0227] Furthermore, the resist underlayer film of this embodiment can also be used as an antireflection film for a common single-layer resist or a base material for suppressing pattern collapse. Since the resist underlayer film of this embodiment has excellent etching resistance for base processing, it can also be expected to function as a hard mask for base processing.
[0228] When forming a resist layer by the above-mentioned known photoresist material, it is preferred to use a wet process such as spin coating, screen printing, etc. in the same manner as forming the aforementioned resist lower film. In addition, after applying the resist material by spin coating, pre-baking is usually performed, and the pre-baking is preferably performed within the range of 80 to 180° C. of baking temperature and 10 to 300 seconds of baking time. Afterwards, according to a conventional method, exposure, post-exposure baking (PEB), and development are performed to obtain a resist pattern. It should be noted that the thickness of each resist film is not particularly limited, and is usually preferably 30 nm to 500 nm, and more preferably 50 nm to 400 nm.
[0229] The exposure light may be appropriately selected according to the photoresist material used, and is generally a high-energy ray with a wavelength of 300 nm or less, and specifically includes 248 nm, 193 nm, 157 nm excimer lasers, 3 to 20 nm soft X-rays, electron beams, X-rays, and the like.
[0230] The resist pattern formed by the above method is one in which pattern collapse is suppressed by the resist underlayer film of this embodiment. Therefore, by using the resist underlayer film of this embodiment, a finer pattern can be obtained, and the exposure amount required to obtain the resist pattern can be reduced.
[0231] Next, the obtained resist pattern is used as a mask for etching. As the etching of the resist lower film in the two-layer process, gas etching is preferably used. As the gas etching, etching using oxygen is preferred. In addition to oxygen, inactive gases such as He and Ar, CO, CO2, NH3, SO2, N2, NO2, and H2 gases may also be added. In addition, gas etching may be performed using only CO, CO2, NH3, SO2, N2, NO2, and H2 gases instead of oxygen. In particular, the latter gas is preferably used for sidewall protection in order to prevent undercutting of the pattern sidewalls.
[0232] On the other hand, the etching of the intermediate layer (the layer between the photoresist layer and the resist lower film) in the three-layer process is also preferably carried out by gas etching. As gas etching, the same as described in the above-mentioned two-layer process can be applied. In particular, the processing of the intermediate layer in the three-layer process is preferably carried out by using a chlorofluorocarbon-based gas to use the resist pattern as a mask. Afterwards, the intermediate layer pattern is used as a mask as described above, for example, by performing oxygen etching, so that the resist lower film can be processed.
[0233] Here, when an inorganic hard mask intermediate layer film is formed as the intermediate layer, a silicon oxide film, a silicon nitride film, or a silicon oxide nitride film (SiON film) is formed by a CVD method, an ALD method, or the like. The method for forming the nitride film is not limited to the following, and for example, the method described in Japanese Patent Application Publication No. 2002-334869 and International Publication No. 2004 / 066377 can be used. A photoresist film can be directly formed on such an intermediate layer film, or an organic anti-reflection film (BARC) can be formed on the intermediate layer film by spin coating, and a photoresist film can be formed thereon.
[0234] As the intermediate layer, an intermediate layer based on polysilsesquioxane may also be preferably used. By making the resist intermediate film have the effect of an anti-reflection film, there is a tendency to effectively suppress reflection. The specific material of the intermediate layer based on polysilsesquioxane is not limited to the following, and for example, those recorded in Japanese Patent Publication No. 2007-226170 and Japanese Patent Publication No. 2007-226204 may be used.
[0235] In addition, the etching of the substrate can also be performed by a common method. For example, if the substrate is SiO2 or SiN, etching can be performed mainly using chlorofluorocarbon gas, and if it is p-Si, Al, or W, etching can be performed mainly using chlorine or bromine gas. When etching the substrate with chlorofluorocarbon gas, the silicon-containing resist of the two-layer resist process and the silicon-containing intermediate layer of the three-layer process are stripped at the same time as the substrate is processed. On the other hand, when etching the substrate with chlorine or bromine gas, the silicon-containing resist layer or the silicon-containing intermediate layer is stripped separately, and generally, dry etching stripping using chlorofluorocarbon gas is performed after the substrate is processed.
[0236] The resist lower layer film of the present embodiment has excellent etching resistance for these substrates. It should be noted that as a substrate, a well-known one can be appropriately selected for use, without particular limitation, and examples thereof include Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al, etc. In addition, the substrate can also be a laminate having a processed film (processed substrate) on a substrate (support). As such a processed film, various Low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si and their termination films can be cited, and materials different from the substrate (support) are usually used. It should be noted that the thickness of the substrate or the processed film to be processed is not particularly limited, and is generally preferably about 50nm to 10,000nm, and more preferably 75nm to 5,000nm.
[0237] The resist lower film of this embodiment has excellent embedding flatness for a substrate with steps. As a method for evaluating embedding flatness, a known method can be appropriately selected and used without particular limitation. For example, a solution of each compound adjusted to a specified concentration can be applied by spin coating on a silicon substrate with steps, and the solvent is removed and dried at 110°C for 90 seconds to form a Te-containing lower film in a manner of a specified thickness. After baking at a temperature of about 240 to 300°C for a specified time, the difference (ΔT) in the thickness of the lower film between the line width & spacing area and the open area without a pattern can be measured by an ellipsometer, thereby evaluating the embedding flatness for the step substrate.
[0238] [Optical article forming composition and cured product thereof]
[0239] The optical component forming composition of the present embodiment is useful for optical materials. The optical component forming composition of the present embodiment can be expected to have high refractive index and high transparency by including the aforementioned polymer or compound containing Te, and can also be expected to have storage stability, structure forming ability (film forming ability), and heat resistance. From the perspective of miniaturization of optical components and improving light collection efficiency, the refractive index of optical articles is preferably above 1.60, more preferably above 1.65, further preferably above 1.70, and further preferably above 1.75. From the perspective of improving light collection efficiency, the transparency of optical articles is preferably above 70%, more preferably above 80%, and further preferably above 90%. The measuring method of refractive index is not particularly limited, and known methods can be used. For example, ellipsometry, minimum deflection angle method, critical angle method (Abbe type, Pulfrich type), V-block method, prism coupling method, and liquid immersion method (Beck line method) can be cited. The measuring method of transparency is not particularly limited, and known methods can be used. For example, spectrophotometer and ellipsometry can be cited.
[0240] Furthermore, the cured product of the present embodiment obtained by curing the optical component forming composition can be a three-dimensional crosslinked product, and coloring is suppressed even by heat treatment in a wide range from low to high temperatures, so that a high refractive index and high transparency can be expected.
[0241] The optical component forming composition of the present embodiment may further contain a solvent in addition to the aforementioned polymer or compound. The solvent may be the same as the solvent used in the aforementioned lithography material composition of the present embodiment.
[0242] In the optical component forming composition of the present embodiment, the relationship between the amount of solid content and the amount of solvent is not particularly limited, and relative to the total of 100 mass% of the solid content and the solvent, preferably 1 to 80 mass% of solid content and 20 to 99 mass% of solvent, more preferably 1 to 50 mass% of solid content and 50 to 99 mass% of solvent, further preferably 2 to 40 mass% of solid content and 60 to 98 mass% of solvent, particularly preferably 2 to 10 mass% of solid content and 90 to 98 mass% of solvent. It should be noted that the optical component forming composition of the present embodiment may not contain a solvent.
[0243] The optical component forming composition of the present embodiment may contain at least one selected from the group consisting of an acid generator (C), an acid crosslinking agent (G), an acid diffusion controller (E), and other components (F) as other solid components.
[0244] In the optical component forming composition of the present embodiment, the content of the aforementioned polymer or compound (the total when used in combination) is not particularly limited, but is preferably 50 to 99.4% by mass of the total mass of the solid component, more preferably 55 to 90% by mass, further preferably 60 to 80% by mass, and particularly preferably 60 to 70% by mass.
[0245] The acid generator (C), acid crosslinking agent (G), acid diffusion controller (E) and other components (F) contained in the optical component forming composition of this embodiment may be the same as those contained in the lithography material composition of the above-mentioned embodiment.
[0246] In the optical component forming composition of the present embodiment, the content of the aforementioned polymer or compound, acid generator (C), acid diffusion control agent (E), and other components (F) (the aforementioned polymer or compound (the total when used in combination) / acid generator (C) / acid diffusion control agent (E) / other components (F)) is preferably 50 to 99.4 / 0.001 to 49 / 0.001 to 49 / 0 to 49, more preferably 55 to 90 / 1 to 40 / 0.01 to 10 / 0 to 5, further preferably 60 to 80 / 3 to 30 / 0.01 to 5 / 0 to 1, and particularly preferably 60 to 70 / 10 to 25 / 0.01 to 3 / 0. The content ratio of each component is selected from each range in such a way that the total becomes 100% by mass. If the above-mentioned content ratio is set, the performance of sensitivity, resolution, developability, etc. will be more excellent.
[0247] The method for preparing the optical component forming composition of the present embodiment is not particularly limited, and examples thereof include a method of dissolving each component in a solvent to prepare a uniform solution, and then filtering the solution using a filter having a pore size of about 0.2 μm as necessary.
[0248] The optical component forming composition of the present embodiment may contain a resin within a range not hindering the purpose of the present invention. The type and amount of the resin may be set as disclosed in Patent Document 1.
[0249] In addition, the cured product of the present embodiment is obtained by curing the aforementioned optical component forming composition, and can be used as various resins. These cured products can be used for various purposes as high-versatility materials that give various characteristics of high melting point, high refractive index and high transparency. It should be noted that the cured product can be obtained by using the known methods corresponding to each composition such as light irradiation and heating of the aforementioned composition.
[0250] These cured products can be used as various synthetic resins such as epoxy resins, polycarbonate resins, and acrylic resins, and can be used as optical parts such as lenses and optical sheets by utilizing their functionality.
[0251] 6. Purification Method
[0252] There is no particular limitation on the purification method of the aforementioned polymer or compound, and the method described in International Publication 2015 / 080240, the method described in International Publication 2018 / 159707, etc. can be used. Specifically, the purification method includes the following steps: dissolving the aforementioned polymer or compound in an organic solvent that is not mixed with water to obtain an organic phase, contacting the organic phase with an acidic aqueous solution to perform an extraction treatment, so that the metal components contained in the organic phase containing the aforementioned polymer or compound and the organic solvent are transferred to the aqueous phase, and then separated into an organic phase and an aqueous phase. An organic solvent that is not mixed with water refers to an organic solvent that is generally classified as a non-water-soluble solvent. As the organic solvent, there is no particular limitation, and it is preferably an organic solvent that can be safely applied to semiconductor manufacturing processes. The amount of the organic solvent used is generally about 1 to 100 times the mass of the compound used.
[0253] Specific examples of the organic solvent used include those described in International Publication No. 2015 / 080240, among which toluene, 2-heptanone, cyclohexanone, cyclopentanone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, ethyl acetate, etc. are preferred, and cyclohexanone and propylene glycol monomethyl ether acetate are particularly preferred.
[0254] As the aforementioned acidic aqueous solution, it can be appropriately selected from aqueous solutions formed by dissolving commonly known organic and inorganic compounds in water. For example, those recorded in International Publication 2015 / 080240 can be cited. These acidic aqueous solutions can be used alone or in combination of two or more. As acidic aqueous solutions, for example, inorganic acid aqueous solutions and organic acid aqueous solutions can be cited. As inorganic acid aqueous solutions, for example, aqueous solutions containing one or more selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid can be cited. As organic acid aqueous solutions, for example, aqueous solutions containing one or more selected from the group consisting of acetic acid, propionic acid, oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, tartaric acid, citric acid, methanesulfonic acid, phenolsulfonic acid, p-toluenesulfonic acid and trifluoroacetic acid can be cited. The pH range of the acidic aqueous solution is about 0 to 5, preferably about pH 0 to 3.
[0255] Example
[0256] [Example 1]
[0257] (1) Synthesis of BPAO
[0258] In a 100 mL eggplant-shaped flask, 20 mmol (4.56 g) of bisphenol A (BPA), 50 mmol (17.63 g) of cesium carbonate, 4.0 mmol (0.64 g) of KI, and 20 mL of DMF were placed and stirred at 80° C. for 1 hour. Next, 30 mmol (3.61 g) of 3-(chloromethyl)-3-methyloxetane (CMO) was added and reacted at 70° C. for 8 hours, and the same amount of CMO was further added and reacted at 70° C. for 8 hours.
[0259] The reaction mixture was filtered, and 1N hydrochloric acid was added to the filtrate to obtain a precipitate. The precipitate was filtered out using a Kiriyama funnel. The precipitate was further subjected to a chromatographic column separation using chloroform to separate a white solid as the target (BPAO). The results are shown below. 1 H-NMR and 13 The C-NMR spectrum is shown in Figure 1 .
[0260] Yield: 7.179 g
[0261] Yield: 90%
[0262] Melting point: 161.0~163.0℃
[0263]
[0264] (2) Synthesis of Poly(BPAO-co-TeCl4)
[0265] BPAO, TeCl4 and a catalyst synthesized as described above were placed in a flask and a polymerization reaction was carried out. The conditions were set as follows.
[0266] Solvent: Chloroform
[0267] Reaction substrate concentration: 1M
[0268] Time: 6h
[0269] Temperature: Room temperature
[0270] Feed ratio (molar ratio): as shown in Table 1
[0271]
[0272] [Table 1]
[0273]
[0274] 1) Based on 1 H-NMR
[0275] 2) Based on SEC (size exclusion chromatography)
[0276] 3) Based on TGA (thermogravimetric analysis)
[0277] The reaction solutions of Run 1 to Run 5 in Table 1 were directly added to deuterated chloroform and measured. 1 The results of H-NMR are shown in Figure 2 Since the raw material conversion rate was 10% in Run 1, the peak (4.4-4.7 ppm) of 3-(chloromethyl)-3-methyloxetane (CMO) derived from the raw material was detected. From Run 2 onwards, the peak derived from CMO decreased as the raw material conversion rate increased, and no peak derived from CMO was observed in Run 5 (raw material conversion rate 100%).
[0278] The obtained unpurified polymer was purified by reprecipitation using ether. The heat resistance of the purified polymer was evaluated. The results are shown in Table 1. The heat resistance was measured using TGA (TGA-50 / 51 manufactured by Shimadzu Corporation, under nitrogen atmosphere, heating rate 10°C / min). d 5% (5 wt% weight loss temperature) for evaluation. 1 H-NMR spectrum is shown in Figure 3 Furthermore, 2 mg of the polymer was dissolved in 2 mL of the following solvent at 20°C, and the state was visually confirmed to conduct a solubility test. The evaluation results are shown in Table 1-1. ++ indicates easy solubility, and - indicates insolubility.
[0279] [Table 1-1]
[0280] Table 1-1
[0281] Solvents Solubility acetone ++ Methanol ++ Ethanol ++ Ethyl acetate ++ Chloroform +- DCM -- MEK ++ THF ++ DMF ++ DMSO ++ Hexane -- water --
[0282] [Example 2]
[0283] The polymer obtained in Run 5 of Example 1 was dissolved in THF to obtain a composition having a concentration of 3% by mass. The solution was spin-coated on a silicon wafer under the following conditions and post-baked to obtain a film. The film forming property was good.
[0284] Speed: 3000rpm
[0285] Time: 5 seconds
[0286] Post-baking: 90°C
[0287] The film thickness was 100 nm, and the refractive index measured using an ellipsometer (measurement wavelength: 636 nm) was 1.60. A photograph of the film is shown at Figure 4 The film thus produced can be suitably used as a resist film, an underlayer film for photolithography, or an optical component.
[0288] [Example 3]
[0289] 3-(Chloromethyl)-3-methyloxetane (CMO) 30mmol (3.61g), TeCl4 15mmol (4.41g), and dichloromethane 10mL were added to a 30mL eggplant-shaped flask and stirred at room temperature for 3 hours to react. Then, the reaction solution was concentrated using an evaporator. Dichloromethane was added to the concentrate and diluted again, and the concentrate was injected into an excess amount of hexane to obtain a precipitate. This reprecipitation operation was repeated 3 times. Then, the precipitate was filtered using a membrane filter to obtain the target (gray solid). The results are shown below.
[0290] Yield: 0.741 g
[0291] Yield: 8%
[0292] The reaction mixture was filtered, and 1N hydrochloric acid was added to the filtrate to obtain a precipitate. The precipitate was filtered out using a Kiriyama funnel. The precipitate was then separated using a chromatographic column using chloroform to separate a white solid as the target product. The results are shown below. 1 The H-NMR spectrum is shown in Figure 5 .
[0293] Yield: 7.179 g
[0294] Yield: 90%
[0295] Melting point: 161.0~163.0℃
[0296]
[0297] [Example 4]
[0298] The following compound tBPO was synthesized by the same method as described in "Synthesis of BPAO" except that p-tert-butylphenol was used instead of bisphenol A. 1 H-NMR shows Figure 6 .
[0299]
[0300] Next, the following compound was obtained by the same method as in Example 3 except that tBPO was used instead of CMO.
[0301]
[0302] [Example 5] Study on the feed ratio of poly(BPAE-co-TeCl2)
[0303] After adding the amount of TeCl4 shown in Table 2 to a 10 mL eggplant flask, nitrogen replacement was performed. The feed ratio in Table 2 is a molar ratio. Next, 1.0 mmol (0.340 g) of bisphenol A glycidyl ether (denoted as BPAE) dissolved in 2.0 mL of chloroform was slowly added to the flask using a syringe. After stirring at room temperature for 5 hours to react, the filtrate was filtered and concentrated. The analysis results are shown in Table 2. The conversion rate is based on 1 H-NMR is used to determine the epoxide groups. Molecular weight and molecular weight distribution are determined by SEC. d 5% (5 wt% weight loss temperature) was determined by TGA (TGA-50 / 51 manufactured by Shimadzu Corporation, under nitrogen atmosphere, heating rate 10°C / min).
[0304]
[0305] [Table 2]
[0306] Table 2
[0307]
[0308] a) Based on 1 Quantitative calculation of epoxy groups by H-NMR
[0309] b) Based on SEC
[0310] c) Based on TGA
[0311] d) Not determined
[0312] It can be seen that the conversion rate increases with the increase in the amount of TeCl4 input, and a feed ratio of 1:1 can achieve a conversion rate of 100%. It can be seen that TeCl4 will undergo a catalytic reaction, and the reaction ratio of epoxide, namely BPAE, to TeCl4 is 1:1. After the reaction is completed, since the polymer solution is viscous, it is believed that a high molecular weight body is obtained, but the results of size exclusion chromatography (SEC) cannot confirm a high molecular weight body. The reason is believed to be the instability of the Te-O bond. In addition, in order to perform SEC measurement, TGA analysis of the precipitate produced when the polymer is dissolved in a solvent is performed. The result is a TGA curve close to that of an inorganic substance. This also suggests the possibility of inorganic tellurium being produced by decomposition in the measurement solvent.
[0313] [Example 6] Study on the feed ratio and solvent of poly(MTPEP-co-TeCl2)
[0314] Put the amount of TeC14 shown in Table 3 into a test tube and replace it with nitrogen. The feed ratio in Table 3 is a molar ratio. Then, use a syringe to slowly add 1.0 mmol (0.460 g) of 4,4',4"-trihydroxytriphenylmethane triglycidyl ether (MTPEP) dissolved in 2.0 mL of chloroform or methyl ethyl ketone (MEK) to the test tube and react it at room temperature for 24 hours. Thereafter, the obtained solution is dropped into ethanol to obtain an orange viscous liquid. 1 As a result of H-NMR, it was confirmed that the peak derived from the epoxide of MTPEP disappeared, and thus it was confirmed that the reaction progressed. The analysis results are shown in Table 3. The analysis was carried out using the method described in Example 5.
[0315]
[0316] [Table 3]
[0317] Table 3
[0318]
[0319] b) Based on SEC (Solvent: DMF with LiBr and H3PO4 dissolved, polystyrene conversion)
[0320] c) Based on TGA
[0321] d) Based on ellipsometry
[0322] e) Cannot be determined using SEC
[0323] f) Not determined
[0324] When the molecular weight of the obtained compound was measured by SEC, it was confirmed that a high molecular weight compound with a molecular weight of 2,600 to 3,600 was obtained. However, when the feed ratio was 1.00 / 2.00 to 1.2.50, the measurement by SEC could not be performed.
[0325] [Example 7] Study on the feed ratio and solvent of poly(MTPOX-co-TeCl2)
[0326] Add the amount of TeCl4 shown in Table 4 to the test tube and replace with nitrogen. The feed ratio in Table 4 is a molar ratio. Use a syringe to slowly add 1.0 mmol (0.544 g) of MTPOX dissolved in 2.0 mL of chloroform or methyl ethyl ketone (MEK) to the test tube and react at room temperature for 24 hours. Then, drop the obtained solution into ethanol to obtain an orange solid. 1 H-NMR spectrum is shown in Figure 7 The analysis results are shown in Table 4. The molecular weight, molecular weight distribution and T were measured as described above. d 5%. Refractive index (n D ) was measured by the method described in Example 2.
[0327]
[0328] [Table 4]
[0329] Table 4
[0330]
[0331] b) Based on SEC (Solvent: DMF with LiBr and H3PO4 dissolved, polystyrene conversion)
[0332] c) Based on TGA
[0333] d) Based on ellipsometry
[0334] e) Cannot be determined using SEC
[0335] f) Not determined
[0336] It is known that when measuring molecular weight by SEC, if MEK is used as solvent, a higher molecular weight body can be obtained. However, the molecular weight distribution is also significantly broadened, so it can be said that it is not suitable as a resist material. In addition, when there is TeCl2 at the end, the possibility of becoming sensitive to moisture is high. According to the above content, considering the situation of being used as a resist material, chloroform is selected as solvent, and the resist properties of the polymer synthesized in Run2 are evaluated below.
[0337] A film was formed by the same method as in Example 2 except that the polymer synthesized in Run 2 was dissolved in THF to prepare a 2 mass % composition.
[0338] Solvent: THF
[0339] Concentration: 2 mass%
[0340] The refractive index and film thickness of the obtained film were evaluated by the same method as in Example 2. The results are shown below.
[0341] Refractive index: 1.584
[0342] Film thickness: 60nm
[0343] The evaluation results of the solubility of the polymer synthesized in Run 2 are shown below. The solubility was evaluated by the same method as in Example 1. The results are shown in Table 5.
[0344] [Table 5]
[0345] Table 5
[0346] Solvents Solubility Chloroform ++ Dichloromethane (DCM) +- Methyl Ethyl Ketone (MEK) ++ Tetrahydrofuran (THF) ++ Propylene glycol monomethyl ether (PGME) ++ Propylene glycol monomethyl ether acetate (PGMEA) ++ Acetonitrile +- Hexane +- Toluene -- Methanol +- Ethyl acetate ++ Ether ++ Tetramethylammonium hydroxide aqueous solution (TMAHaq) --
[0347] (Synthesis Comparative Example 1)
[0348] Prepare a four-necked flask with a Dimroth cooling tube, a thermometer, and a stirring blade, and a detachable bottom with an internal volume of 10L. In a nitrogen stream, 1.09kg (7mol, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 2.1kg (28mol as formaldehyde, manufactured by Mitsubishi Gas Chemical Co., Ltd.) of 40% by mass formaldehyde aqueous solution, and 0.97mL of 98% by mass sulfuric acid (manufactured by Kanto Chemical Co., Ltd.) of 1,5-dimethylnaphthalene are added to the four-necked flask, and the mixture is refluxed at 100°C under normal pressure and reacted for 7 hours. After that, 1.8kg of ethylbenzene (special grade reagent manufactured by Wako Pure Chemical Industries, Ltd.) as a diluent solvent is added to the reaction solution, and the lower aqueous phase is removed after standing. Then, neutralization and water washing are performed, and 1.25kg of dimethylnaphthalene formaldehyde resin as a light brown solid is obtained by distilling off ethylbenzene and unreacted 1,5-dimethylnaphthalene under reduced pressure. The molecular weight Mn of the obtained dimethylnaphthalene formaldehyde is 562.
[0349] Next, prepare a 0.5L four-necked flask equipped with a Dimroth cooling tube, a thermometer and a stirring blade. In the four-necked flask, 100g (0.51mol) of the above-mentioned dimethylnaphthalene formaldehyde resin and 0.05g of p-toluenesulfonic acid are added under a nitrogen flow, heated to 190°C for 2 hours and then stirred. Thereafter, 52.0g (0.36mol) of 1-naphthol is further added, and the temperature is raised to 220°C to react for 2 hours. After solvent dilution, neutralization and water washing are carried out, and the solvent is removed under reduced pressure to obtain 126.1g of modified resin (CR-1) as a dark brown solid. The obtained resin (CR-1) has Mn: 885, Mw: 2220, and Mw / Mn: 4.17. Mn, Mw and Mw / Mn of the resin (CR-1) are determined by gel permeation chromatography (GPC) analysis under the following measurement conditions in terms of polystyrene.
[0350] Device: Shodex GPC-101 (Showa Denko K.K.)
[0351] Chromatographic column: KF-80M×3
[0352] Eluent: THF 1mL / min
[0353] Temperature: 40℃
[0354] (Synthesis Example 1) Synthesis of AC-1
[0355] A reaction solution was prepared by dissolving 4.15 g of 2-methyl-2-methacryloyloxyadamantane, 3.00 g of methacryloyloxy-γ-butyrolactone, 2.08 g of 3-hydroxy-1-adamantyl methacrylate, and 0.38 g of azobisisobutyronitrile in 80 mL of tetrahydrofuran. The reaction solution was stirred under a nitrogen atmosphere and the temperature was maintained at 63° C. for polymerization for 22 hours. Thereafter, the reaction solution was dropped into 400 mL of n-hexane. The purified resin was solidified, the generated white powder was filtered, and then dried overnight at 40° C. under reduced pressure to obtain AC-1 shown in the following formula.
[0356]
[0357] In Formula AC-1, "40", "40" and "20" represent the ratio of each structural unit, and do not mean that it is a block copolymer.
[0358] [Example A, Comparative Example A]
[0359] Using the following compounds or polymers, photoresist film-forming compositions (resist film-forming compositions) having the compositions shown in Table 6 were prepared.
[0360] The resin Poly(BPAO-co-TeCl4) obtained in Example 1
[0361] Compound (T1) obtained in Example 3
[0362] Compound (T2) obtained in Example 4
[0363] Poly(BPAE-co-TeCl2) obtained in Example 5
[0364] Poly(MTPEP-co-TeCl2) obtained in Example 6
[0365] Poly(MTPOX-co-TeCl2) obtained in Example 7
[0366] CR-1
[0367] The following were used for the acid generator, the acid diffusion controller, the acid crosslinking agent, and the organic solvent. In Table 6, the values in parentheses are the blending amounts (parts by mass).
[0368] <Acid Generator>
[0369] Triphenylsulfonium trifluoromethanesulfonate (TPS-109 (trade name)) manufactured by Midori Kagaku Co., Ltd.
[0370] Midori Kagaku Co., Ltd. Di-tert-butyldiphenyliodonium nonafluorobutane sulfonate (DTDPI)
[0371] Pyridinium p-toluenesulfonate manufactured by Kanto Chemical Co., Ltd. (referred to as "PPTS" in the table)
[0372] <Acid Diffusion Controller>
[0373] Tri-n-octylamine (TOA, manufactured by Kanto Chemical Co., Ltd.)
[0374] <Acid crosslinking agent>
[0375] NIKALAC MW-100LM (MW-100LM, trade name, manufactured by SANWA Chemical Co., Ltd.)
[0376] NIKALAC MX270 manufactured by SANWA Chemical Co., Ltd.
[0377] TMOM-BP manufactured by Honshu Chemical Industry Co.,Ltd.
[0378] <Organic Solvents>
[0379] Propylene glycol monomethyl ether (PGME, manufactured by Kanto Chemical Co., Ltd.)
[0380] [Table 6-1]
[0381] Table 6
[0382]
[0383] [Table 6-2]
[0384] Table 6 (follow-up)
[0385]
[0386] [Evaluation method]
[0387] (1) Thin film formation of resist film-forming composition
[0388] After preparing the resist film forming composition according to the composition described in Table 6, the resist film forming composition in a uniform state was spin-coated on a clean silicon wafer. After that, a pre-exposure bake (PB) was performed in an oven at 110° C. to form a resist film with a thickness of 40 nm. Regarding the resist film, when the thin film was formed well, it was evaluated as G, and when the formed film had defects, it was evaluated as N.
[0389] (2) Resist pattern
[0390] Each resist film obtained in the above (1) was irradiated with electron beams at a line and space setting of 1:1 at a spacing of 50 nm using an electron beam drawing apparatus (ELS-7500, manufactured by Elionix Inc., 50 keV). After irradiation, the resist films were heated at 110° C. for 90 seconds and immersed in a developer of propylene glycol monomethyl ether (PGME) for 60 seconds for development. Thereafter, each resist film was washed with ultrapure water for 30 seconds and dried to form a resist pattern.
[0391] The shape of the obtained resist pattern with L / S (1:1) at a spacing of 50 nm was observed using an electron microscope (S-4800, trade name) manufactured by Hitachi, Ltd. The shape of the resist pattern after development was evaluated based on the following criteria.
[0392] A: There is no pattern collapse, and the rectangularity is better than that of Comparative Example A1.
[0393] B: The rectangularity is better than that of Comparative Example A1, but 1 to 2 pattern collapses are found within the range of 1 μm×1.5 μm.
[0394] B': Three or more pattern collapses were found within a range of 1μm×1.5μm
[0395] C: Equal to or worse than Comparative Example A1
[0396] In addition, in Comparative Example A1, regarding the resist pattern shape after development, pattern collapse and poor rectangularity were observed.
[0397] (3) Etching resistance
[0398] Each resist film obtained in the aforementioned evaluation method (1) was subjected to an etching test, and the etching rate at this time was measured. In addition, in the composition shown in Table 6, a novolac resin (PSM4357 (model) manufactured by Gun Ei Chemical Industry Co., Ltd.) was used instead of Poly (BPAO-co-TeCl4) in Example A1 to prepare a comparative composition. Regarding this comparative composition, a resist film was prepared by the same method as in the aforementioned (1), and an etching test was also performed on the resist film. The etching conditions are as follows.
[0399] (Etching conditions)
[0400] Etching device: RIE-10NR (trade name) manufactured by Samco Inc.
[0401] Output: 50W
[0402] Pressure: 20Pa
[0403] Time: 2 minutes
[0404] Etching gas: Ar gas flow: CF4 gas flow: O2 gas flow = 50:5:5 (sccm)
[0405] The etching resistance of each resist film was evaluated according to the following evaluation criteria, using the etching rate of the resist film obtained from the comparative composition using the novolac resin as a reference.
[0406] (Evaluation Criteria)
[0407] A: The etching rate is lower than -15% compared with the novolac resin resist film.
[0408] B: The etching rate is -15% to +5% compared to the novolac resin resist film.
[0409] C: The etching rate is higher than +5% compared with the resist film of novolac resin.
[0410] Table 7 shows these evaluation results.
[0411] [Table 7]
[0412] Table 7
[0413]
[0414] It is found that the composition of Example A can form an excellent resist pattern and can form a film having excellent etching resistance.
[0415] [Example B, Comparative Example B]
[0416] (1) Formation of resist underlayer film
[0417] Using a Te-containing compound or a Te-containing polymer in the same manner as in Example A, resist underlayer film-forming compositions having the compositions shown in Table 8 were prepared. Next, these resist underlayer film-forming compositions were spin-coated on a silicon substrate, and then baked at 240° C. for 60 seconds and then at 400° C. for 120 seconds to prepare resist underlayer films having a film thickness of 70 nm. The following were used for the acid generator, the acid crosslinking agent, and the organic solvent.
[0418] <Acid Generator>
[0419] Di-tert-butyldiphenyliodonium nonafluoromethanesulfonate (referred to as "DTDPI" in the table) (manufactured by Midori Kagaku Co., Ltd.)
[0420] Triphenylsulfonium trifluoromethanesulfonate (TPS-109 (trade name)) (manufactured by Midori Kagaku Co., Ltd.)
[0421] Pyridinium p-toluenesulfonate manufactured by Kanto Chemical Co., Ltd. (referred to as "PPTS" in the table)
[0422] <Acid crosslinking agent>
[0423] "NIKALAC MX270" (referred to as "MX270" in the table) (product name, manufactured by SANWA Chemical Co., Ltd.)
[0424] "NIKALAC MW-100LM" (described as "MW-100LM" in the table) (trade name, manufactured by SANWA Chemical Co., Ltd.)
[0425] TMOM-BP manufactured by Honshu Chemical Industry Co.,Ltd.
[0426] <Organic Solvents>
[0427] Propylene glycol monomethyl ether (also referred to as "PGME" in the table)
[0428] [Table 8-1]
[0429] Table 8
[0430]
[0431] [Table 8-2]
[0432] Table 8 (follow-up)
[0433]
[0434] (2) Formation and evaluation of anti-corrosion film
[0435] An ArF resist solution was applied to the resist underlayer film formed in the above (1) and baked at 130°C for 60 seconds to form a photoresist film with a film thickness of 140 nm. The ArF resist solution was prepared by mixing 5 parts by mass of the resin (AC-1) obtained in the above Synthesis Example 1, 1 part by mass of triphenylsulfonium nonafluoromethanesulfonate, 2 parts by mass of tributylamine and 92 parts by mass of PGMEA.
[0436] Next, the photoresist film was exposed using an electron beam drawing apparatus "ELS-7500" (product name, manufactured by Elionix Inc., 50 keV), then baked (PEB) at 115° C. for 90 seconds, and developed for 60 seconds using a 2.38 mass % tetramethylammonium hydroxide (TMAH) aqueous solution to obtain a positive resist pattern.
[0437] The results of the defects of the 55 nmL / S (1: 1) and 80 nmL / S (1: 1) resist patterns obtained by observation are shown in Table 9. In the table, "good" shown as the result of "resist pattern after development" means that no pattern collapse is found in the formed resist pattern, and "bad" means that pattern collapse is found in the formed resist pattern. In addition, in the above-mentioned observation results, the minimum line width with no pattern collapse and good rectangularity is used as an index for evaluating "resolution". Furthermore, the minimum electron beam energy that can depict a good pattern shape is used as an index for evaluating "sensitivity". The results are shown in Table 9.
[0438] [Comparative Example B1]
[0439] A photoresist film was directly formed on the SiO 2 substrate in the same manner as in Example B1 except that the underlayer film was not formed, thereby obtaining a positive resist pattern.
[0440] [Table 9-1]
[0441] Table 9
[0442]
[0443] [Table 9-2]
[0444] Table 9 (follow-up)
[0445]
[0446] It is found that the composition of Example B can form a highly sensitive film.
Claims
1. A polymer having tellurium in its main chain, which is obtained by reacting (A) a compound having a plurality of cyclic (thio)ether groups with (B) TeX4, wherein X is a halogen atom.
2. The polymer according to claim 1, wherein The (A) is a compound represented by formula (A1), Where n is 2 to 4, W is an organic group having 10 to 30 carbon atoms, The cyclic structure containing Z is a group having a cyclic ether or cyclic thioether group, Z is O or S.
3. The polymer according to claim 2, wherein The W is a group represented by -Z-Ar-Z-, Ar is an organic group having an aromatic ring or a heterocyclic ring.
4. The polymer according to claim 3, wherein The Ar is a group represented by -Ar'-U-Ar'-, Ar' is an aromatic group or a heterocyclic aromatic group, U is a divalent organic group or a single bond.
5. The polymer according to claim 1 or 2, wherein The cyclic (thio)ether group of (A) has a 3- to 5-membered ring structure. 6 . A method for producing the polymer according to claim 1 , comprising the step of subjecting the (A) and the (B) to an addition reaction.
7. The manufacturing method according to claim 6, wherein: The reaction is carried out in the presence of a Lewis acid.
8. A composition comprising the polymer according to claim 1 or 2.
9. The composition according to claim 8, comprising a component selected from the group consisting of a solvent, an acid generator, an acid cross-linking agent, and a combination thereof. 10 . A resist film formed from the composition according to claim 8 .
11. A pattern forming method, comprising: A film forming step of forming a film on a substrate using the composition according to claim 8; an exposure step of exposing the film to light; and A developing step is to develop the film exposed in the exposure step to form a pattern. 12 . An underlayer film for lithography, formed using the composition according to claim 8 . 13 . An optical component formed using the composition according to claim 8 .
14. A tellurium-containing compound obtained by reacting (a) a compound having one cyclic (thio)ether group with (B) TeX4, wherein X is a halogen atom.
15. A composition comprising the tellurium-containing compound according to claim 14.
16. A purification method comprising: A step of dissolving the tellurium-containing polymer according to claim 1 or 2 or the tellurium-containing compound according to claim 14 in a solvent to obtain a solution, wherein the solvent comprises an organic solvent that is immiscible with water; and The first extraction step is to bring the obtained solution into contact with an acidic aqueous solution to extract impurities in the polymer or compound.
Citation Information
Patent Citations
Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof
JP2002334869A
Antireflection film material, substrate having antireflection film and pattern forming method
JP2007226170A
Antireflection film material, substrate and patterning process
JP2007226204A
Ultra-high selectivity ashing-removable hard mask film
JP2013526783A
Method of CVD for forming silicon nitride film on substrate
WO2004066377A1
